2007
DOI: 10.1007/s00394-007-0688-1
|View full text |Cite
|
Sign up to set email alerts
|

Peanuts improve blood glutathione, HDL-cholesterol level and change tissue factor activity in rats fed a high-cholesterol diet

Abstract: Peanut consumption improved GSH and HDL-C levels and decreased TBARS, without increasing other blood lipids in experimental hyperlipidemia. Nevertheless the mechanism of the effect of peanut consumption on the TF activity of tissues remains to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 35 publications
0
12
0
2
Order By: Relevance
“…Besides blood, various tissues and body fluids (saliva, amniotic fluid, bile, semen, sweat or tears) have been known to have TF activity [20][21][22][23][24][25] . Most of them are not easily obtained; thus, saliva is especially suitable for study because of its ready availability.…”
mentioning
confidence: 99%
“…Besides blood, various tissues and body fluids (saliva, amniotic fluid, bile, semen, sweat or tears) have been known to have TF activity [20][21][22][23][24][25] . Most of them are not easily obtained; thus, saliva is especially suitable for study because of its ready availability.…”
mentioning
confidence: 99%
“…Again, some investigators observed that peanut consumption significantly improve the antioxidant-oxidant status by increasing glutathione peroxidase (GSH) and decreasing thiobarbituric acid reactive substance (TBARS) levels 24 . High level of L-arginin and vitamine E content of peanut also have antioxidant activity and scavange oxygen free radicals thereby preserve normal histological architecture of heart 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to chickpea, phenolics from peanut seeds and particularly peanut skin have high antifungal and antioxidative activity [13][14][15]. Positive effect of peanut on human health can be confirmed by the studies of Emekli-Alturfan et al [16], who ascertained that addition of peanut to the diet did not significantly change blood lipids, protrombin time, activated partial thromboplastin time, or fibrinogen levels, both in control and in hyperlipidemic groups. Peanut consumption improved glutathione (GSH) and high-density lipoprotein (HDL-C) levels and decreased thiobarbituric acid reactive substances (TBARS), without increasing other blood lipids in experimental hyperlipidemia.…”
Section: Introductionmentioning
confidence: 92%